EVALUASI PENERAPAN SAK ETAP DALAM PENYUSUNAN LAPORAN KEUANGAN STARTUP - -, Umi Ariskaningtias; Pusposari, Devy (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
PT Rise Lanskap Hortikultura, a startup in landscaping service LLC, is unexceptionally obliged to prepare its financial reports under SAK ETAP (Indonesian Accounting Standards for Non-Publicly-Accountable Entities). However, the company has had incomplete financial reports and imbalance balance sheet since December 2021. As such, this phenomenon is interesting to study on how financial reports are prepared in a startup; and this study aims to determine the financial reporting of PT Rise Lanskap Hortikultura and its conformity with SAK ETAP, employing descriptive qualitative method with a case study approach. Data are collected from interviews and documentation. This study found that the Financial reports for December 2022 were not in accordance with SAK ETAP. The presentation of the income statement and balance sheet was incomplete, there were discrepancies in cash flow statements, and there was no report on changes in equity and notes on the financial statements. The discrepancy resulted from the lack of an appropriate transaction recording system and incomplete supporting documents. It is expected that startups or similar entities are capable of developing accounting cycle according to their business processes. Future researchers can examine the application of SAK ETAP to startups in different business sectors or the importance of accounting standards for startups.